2008
DOI: 10.1007/s10611-007-9091-3
|View full text |Cite
|
Sign up to set email alerts
|

Cadre recruitment and corruption: what goes wrong?

Abstract: Why do so many corrupt officials rise up in the Chinese official hierarchy in the first place? This paper addresses this question by looking at corruption in the cadre recruitment system as a source of the problem. It attempts to show that despite meaningful reforms to improve cadre recruitment, especially through greater input and supervision from below, these reforms have not succeeded in fundamentally reshaping cadre incentives in the direction of accountability towards the below. Rather, the reforms have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Without a concept of neutral competence, meritocracy could be seriously abused. Sun () found that meritocracy rules are just taken as formalities at local governments. In the nomination and scrutinization stage, for instance, the party secretary and the party Organization Department may set criteria tailored for a target candidate, then look for the ‘right fit’, before going through the formal procedures to legitimize the selection.…”
Section: Case Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a concept of neutral competence, meritocracy could be seriously abused. Sun () found that meritocracy rules are just taken as formalities at local governments. In the nomination and scrutinization stage, for instance, the party secretary and the party Organization Department may set criteria tailored for a target candidate, then look for the ‘right fit’, before going through the formal procedures to legitimize the selection.…”
Section: Case Findings and Discussionmentioning
confidence: 99%
“…Second, consequently, at the operational level, the principle of meritocracy has repeatedly been undermined especially by those in leading positions able to exercise authority as if their views represent party policies or decisions. In other words, those universal rules of public HRM have not been well accepted and respected or strictly observed and adhered to by officials with many continuing improper and illegal practices (Burns and Wang ; Heberer and Trappel ; Sun ).…”
Section: Meritocracy In China – a Historical Reviewmentioning
confidence: 99%
“…Under the local party committee, the chief and deputy chiefs of different party and government branches, legislative and political consultative bodies, state‐owned enterprises, and other public institutions also wield substantial power within each functional unit. Altogether, these key party and state cadres constitute local leadership in China (Sun ). Therefore, the local government structure in China is conducive to predictable corruption because a relatively small number of political leaders is maintained within each subnational governmental jurisdiction.…”
Section: Power Structure and Leadership Stability In China's Local Statementioning
confidence: 99%
“…In their view, personal relationships often serve as the basis for preferential treatment or access to valued goods, information and government positions (see [35]). In examining the failure of reforms in China's personnel recruitment, Sun [25] characterized the current political and economic systems in China as crony capitalism built on a kinship alliance.…”
Section: Structural Opportunitiesmentioning
confidence: 99%